'We Can Tell Them to Get Lost, but We Won't Do That': Cultural Control and Resistance in Voluntary Work. Issue 1 (January 2016) - O' Toole, Michelle; Grey, Christopher
Although cultural control and resistance in organizations have been widely researched, this has invariably been within the context of paid work. This paper examines how they operate within voluntary work, using the case of the Royal National Lifeboat Institution (RNLI). Here, volunteers undertake the dangerous work of sea rescues, working for local lifeboat stations. While the RNLI deploys standard techniques of cultural control, the combination of volunteering, localism and dangerous work creates the possibility of complex and ambiguous forms of resistance to cultural control, thereby extending our understanding of these phenomena.